Living in the municipality of Paraty-RJ: Weaving tradition and valuing traditional and cultural knowledge in the rural and urban context - Edinilson Dos Anjos Silva; Marcele Camargo Ramos; Aline Maria Tomaz Evaristo; Sandra Regina Gregorio (Universidade Federal do Norte do Tocantins, 2022)
This article deals with traditional urban-rural peoples and communities. The Traditional knowledge is the knowledge and practices of rural and local communities associated with biological resources and it is part of the community's identity. This work aims to identify the tradition and value traditional knowledge in the rural-urban context at the municipality of Paraty, State of Rio de Janeiro, seeking to do a dialogic reflection with authors who present and discuss this theme. The field research was made on several rural locations and at the city of Paraty-RJ, to contextualize the rural-urban reference contributing to the biodiversity and quality of life placed on this space. The methodology used is based on the assumptions of qualitative research with ethnographic characteristics and the instruments used to produce the data were field visits, interviews, field diary, photographic records, videos and participant observation. The results obtained allowed an approximation of school contents and daily reality in the rural-urban context, through contextualization. With that, we saw that traditional knowledge is vital for a rural-urban community, as learning, although being continuous, it can preserve identity over time, as well as generating income and giving voice to the communities surveyed.